Optimal Design and Performance Analysis for the Multistage Transmission System of Dispatch Winch based on Volume Optimization - Zhang Xi; Li Bingwen; Hao Ya; Liu Yufei (Jixie chuandong, 2019)
The multi-constraint optimization design for the bevel gear-NGW planetary gear train-cylindrical gear transmission system of dispatch winch is conducted. The minimized overall volume of the transmission system is regarded as the objective function,and based on this,the multi-constraint condition is constructed,which comprehensively considers the teeth,modulus condition,transmission ratio,contact ratio,contact strength,bending strength,diameter of axle and structure conditions. The Fmincon function in MATLAB is used to solve the multi-constraint optimization. The optimization results of design variables and optimization parameters of all transmission subsystem are obtained,and it indicates that the volume of the transmission system decreased by 32. 59% after optimization. Based on this,the 3D model and finite element analysis model of the transmission system are established. According to the modal analysis of the optimized transmission system,it verifies that the optimization results can simultaneously satisfy the optimal volume and stability criteria. The results can provide reference for the optimal design of the transmission system of dispatch winch.